Analisis Pengaruh Ketidakstabilan Debit Air Dan Curah Hujan Terhadap Daya Pada Pembangkit Listrik Tenaga Mini Hidro (PLTM) Karo Bumi Energi - Eko Toni Hagler Simamora; Parlin Siagian; Rahmaniar (Jurnal Serambi Engineering, 2024)
Mini hydro power plants (PLTM) are capable of producing electricity continuously for 24 hours. The amount of energy distributed by the Mini Hydro Power Plant (PLTM) is greatly influenced by the strong flow of water coming from upstream, so the effect of rainfall is relatively direct on the electricity produced by the Karo Bumi Energi Mini Hydro Power Plant (PLTM) with a capacity of 2 x 4, 85 MW. From the observations, rainfall is a dry month, it can also be seen that rainfall, water discharge and production are directly proportional. In May, June and July there is a very significant difference between production and water discharge. According to observations, these months are wet months with very high rainfall. The resulting productivity of hydropower plants is influenced by the creation and release of stable water without aggravation. The higher the creation and release of water, the higher the efficiency of the power supplied. The impact of high rainfall will cause the water release to reach 11,653m3 / hour